2016
DOI: 10.1080/19420862.2016.1236165
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a phosphorylated glycine-serine linker in an IgG-based fusion protein

Abstract: Molecular mass determination by electrospray ionization mass spectrometry of a recombinant IgG-based fusion protein (mAb1-F) produced in human embryonic kidney (HEK) cells demonstrated the presence of a dominant +79 Da product variant. Using LC-MS tryptic peptide mapping analysis and collision-induced dissociation (CID) and electron-transfer/higher-energy collision dissociation fragmentations, the modification was localized to the C-terminal serine residue of a glycine-serine linker [(G4S)2] of a fused heavy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Phosphorylation also occurred on the last serine of a glycine‐serine linker, although the linker had only two repeats of GGGGS, (GGGGS) 2 , and the linker was on the C‐terminus of an Fc domain. The authors also found that the phosphorylation level was much higher for proteins expressed by HEK293 cells (11.3%) than that expressed by CHO cells (0.4%) . In our study, we found that CHO cells can also give high phosphorylation (>20%) on the last serine of a glycine‐serine linker, Ser46.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Phosphorylation also occurred on the last serine of a glycine‐serine linker, although the linker had only two repeats of GGGGS, (GGGGS) 2 , and the linker was on the C‐terminus of an Fc domain. The authors also found that the phosphorylation level was much higher for proteins expressed by HEK293 cells (11.3%) than that expressed by CHO cells (0.4%) . In our study, we found that CHO cells can also give high phosphorylation (>20%) on the last serine of a glycine‐serine linker, Ser46.…”
Section: Discussionsupporting
confidence: 61%
“…For a CHO cell line developed in‐house that produces a GLP1‐Fc fusion protein, we identified partial phosphorylation of the last serine of the (GSSSS) 3 linker. There was only one previous report on the phosphorylation of fusion proteins . Phosphorylation also occurred on the last serine of a glycine‐serine linker, although the linker had only two repeats of GGGGS, (GGGGS) 2 , and the linker was on the C‐terminus of an Fc domain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Even short non-repeating linkers may contain PTMs, such as the phosphorylated serine residue identified in a G4S linker of a fusion protein by Tsyhchuk. 15 This undesirable product heterogeneity prompted us to explore new linker sequences that have better properties.…”
Section: Introductionmentioning
confidence: 99%